Analisis Bibliometrik Tren Kajian Preferensi Konsumen Komoditas Buah Segar di Indonesia - Napitupulu, Tia Sofiani; Sumarlina, Sumarlina; Husnudin, Uni Baroroh (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The study of consumer preferences is a major consideration in determining production and marketing strategies, including for fresh fruit products. This research aims to examine trends in studies on consumer preferences in the marketing of fresh fruits in Indonesia. The study was conducted using bibliometric analysis of data from studies over the period 2013-2023 from the Google Scholar database. Data collection was carried out using the Publish or Perish application by applying an appropriate keyword strategy as a form of selection. Subsequently, mapping and visualization of the analysis results were performed using the VOSviewer application. The analysis results show that the number of publications on consumer preferences for fresh fruits has significantly increased in the last decade, with the main focus on product attributes such as freshness, price, and taste. Studies on consumer preferences for fresh fruits in Indonesia predominantly focus on understanding consumer preferences, product attributes, and data collection methods. The most frequently appearing keywords reflect a strong interest in consumer preferences for local fruits compared to imported ones. The findings of this study open opportunities for further research, particularly in low-density areas such as specific geographical and demographic focuses and certain types of fruits that show potential for further study.